Insect conservation biology : proceedings of the Royal Entomological Society's 23nd symposium (CABI, 2007)
These proceedings contain papers on insect conservation biology that are classified under 3 themes: (1) the current status of insect conservation, and major avenues for progress and hindrances (6 papers); (2) insects as model organisms in conservation biology (6 papers); and (3) future directions in insect conservation biology (6 papers).